Ứng dụng trí tuệ nhân tạo tạo sinh trong dạy học viết bài văn nghị luận về một vấn đề của đời sống ở lớp 8 - Lê, Thị Minh Nguyệt; Nguyễn, Thị Thu Trang (Tạp chí Giáo dục, 2025)
Generative artificial intelligence (Gen AI) has a profound impact on all aspects of human life, and education is no exception. In reality, teaching writing poses considerable challenges for Literature teachers, as 8th-grade students still show significant limitations in their ability to compose social argumentative essays. Gen AI tools offer great potential for application in writing instruction, aiming to enhance teaching effectiveness. In this paper, we propose a set of principles, procedures, and methods for applying selected generative AI tools in teaching students how to write argumentative essays on social issues, with the goal of developing their writing competence in alignment with the competency-based education approach. The research findings provide valuable implications for future studies on integrating artificial intelligence technologies into the development of writing skills among lower secondary students, thereby addressing the current needs of Literature instruction in schools.